Penggunaan Shock Index sebagai Prediktor MODS pada Pasien Multi-trauma di RSUP Prof. Dr. R. D. Kandou Manado - Senjaya, Yan; Lahunduitan, Ishak; Tjandra, Djony (Jurnal Biomedik : JBM, 2018)
Abstract: Multiple organ dysfunction syndrome (MODS) is the leading cause of mortality in patients that still survive in several hours post trauma. Shock index (SI) has been proved to be useful in the early diagnosis of acute hypovolemia in normal blood pressure and pulse condition. It is used to determine the severity of injury and poor outcome in traumatic patient. This study was aimed to obtain the cut-off point ratio of SI which can be used to predict the occurence of MODS and to determine the sensitivity and specificity of SI as a predictor of MODS in multitrauma patients at Prof. Dr. R. D. Kandou Hospital Manado. This was a diagnostic test study with a cross sectional design conducted from Febuary 2016 to May 2017. Population and samples were all multitrauma patients during that period of time that met the inclusion criteria. Data were analyzed by using cut-off point analysis to obtain the area under curve (AUC), as well as the sensitivity and specificity of SI to MODS. There were 150 multitrauma patients in this study, most were males, with the mean age of 33.99 years. The mean ISS was 28.4, SIRS as many as 68.66%, and the mean shock class was 1.4. There were 63 patients with MODS, 37 patients needed PRC transfusion, and 16 patients died. The AUC 80.5% (95% CI 73.0-88.0%; P = 0.000); SI 0.950588 with the sensitivity 74.6% and specificity 78.2% to MODS. The AUC 74.1% (95% CI 61.1-87.2%; P = 0.002); SI 0.97559 with 75.0% sensitivity and 64.2% spesificity to death. Conclusion: Shock index can be used as a predictor of the occurence of MODS and death in multi-trauma patients.Keywords: SI, MODS, multitraumaAbstrak: Multiple organ dysfunction syndrome (MODS) merupakan penyebab utama mortalitas pada pasien yang selamat dalam beberapa jam setelah trauma. Shock index (SI) bermanfaat untuk mendiagnosis awal hipovolemia akut pada keadaan tekanan darah dan nadi yang normal dan digunakan sebagai penanda keparahan suatu cedera dan keluaran yang buruk untuk pasien trauma. Penelitian ini bertujuan untuk mendapatkan cut off point ratio SI yang dapat digunakan sebagai pedoman untuk memrediksi terjadinya MODS dan menentukan sensitivitas dan spesifitas SI sebagai prediktor MODS pada pasien multitrauma di IRDB RSUP Prof. Dr. R. D. Kandou, Manado. Jenis penelitian ialah uji diagnostik dengan desain potong lintang yang dilakukan mulai bulan Febuari 2016 sampai Mei 2017. Populasi dan sampel ialah semua pasien multitrauma yang memenuhi kriteria inklusi. Analisis data menggunakan analisis cut-off point serta mencari area under curve (AUC), sensitivitas, dan spesifitas instrumen SI terhadap MODS. Terdapat 150 pasien multitrauma dalam studi ini, sebagian besar berjenis kelamin laki-laki dengan rerata usia 33,99 tahun. Rerata ISS 28,4, SIRS sebanyak 68,66%, dan rerata syok kelas 1.4. Terdapat 63 pasien multitrauma mengalami MODS, 37 pasien memerlukan transfusi PRC, dan 16 pasien meninggal. Nilai AUC 80,5% (95% interval kepercayaan [IK] 73,0-88,0%; P = 0,000); SI 0,950588 dengan sensitivitas 74,6% dan spesifisitas 78,2% terhadap MODS. Nilai AUC 74,1% (95% interval kepercayaan [IK] 61,1-87,2%; p = 0,002); SI 0,97559 memiliki sensitivitas 75,0% dan spesifisitas 64,2% terhadap terjadinya kematian. Simpulan: Shock index dapat digunakan sebagai prediktor terjadinya MODS dan kematian pada pasien dengan multitrauma.Kata kunci: SI, MODS, multitrauma